1 Answer | Add Yours
You need to remember that changing the sign between the two terms yields the conjugate of the number. Hence, supposing that the number is of form `a + sqrt b` , thus the conjugate is `a - sqrt b` .
Hence, reasoning by analogy, the conjugate of `x+sqrt y` is `x - sqrt y` .
Performing the multiplication between the number and its conjugate yields a diference of two squares, such that:
`(x+sqrt y)(x-sqrt y) = x^2 - (sqrt y)^2`
`(x+sqrt y)(x-sqrt y) = x^2 - y`
Considering the number `2 - sqrt 3` , hence its conjugate is `2 + sqrt 3` and performing the multiplication yields:
`(2 - sqrt 3)(2+ sqrt 3) = 2^2 - (sqrt3)^2 = 4 - 3 =1`
Hence, performing the multiplications of the given numbers by its conjugates yields `(x+sqrt y)(x-sqrt y) = x^2 - y` and `(2 - sqrt 3)(2 + sqrt 3) = 1` .
We’ve answered 317,697 questions. We can answer yours, too.Ask a question